Dampak Penyebaran Data Pribadi melalui Media Digital terhadap Perlindungan Hak Privasi: The Impact of the Distribution of Personal Data via Digital Media on the Protection of Privacy Rights - Pakaya, Putri Regina S; Imran, Suwitno Yutye; Apripari, Apripari (Information Technology and Science (ITScience), 2026)
The development of digital media has driven a significant increase in the exchange and dissemination of personal data in cyberspace. This situation has serious implications for the protection of the right to privacy as a human right. This study aims to analyse the impact of the dissemination of personal data through digital media on the effectiveness of privacy protection and law enforcement practices. The research method used is empirical legal research with a qualitative approach. Data were obtained through interviews with law enforcement officials and community respondents, observations of digital media activities, digital media user questionnaires, and documentation studies of reports and handling of personal data breach cases. The results show that the high intensity of digital media use is not matched by adequate legal awareness and literacy, thus increasing the risk of misuse of personal data. Enforcement of the Personal Data Protection Law has not been optimal due to technical obstacles, limited legal resources, and the tendency to use alternative regulations. The dissemination of personal data also has significant social and psychological impacts on victims, including stigma, social pressure, and prolonged trauma. Therefore, protecting the right to privacy in the digital space requires strengthened law enforcement, increased public digital legal literacy between the state, law enforcement officials, and electronic system administrators.